Measurement of the anomalous magnetic and electric dipole moments of the tau lepton - Acciarri, M; Adriani, O; Aguilar-Benitez, M; Ahlen, S; Alcaraz, J; Alemanni, G; Allaby, J; Aloisio, A; Alviggi, MG; Ambrosi, G; Anderhub, H; Andreev, V; et al. (1998)
We analyse e+e-→ ττγ events using 100pb-1 of data collected by the L3 experiment during the 1991-1995 LEP runs at the Z pole. From the energy of the photons and their isolation from the tau decay products, we determine the anomalous magnetic and electric dipole moments of the tau to be, respectively: aτ = 0.004 ± 0.027 ± 0.023; dτ = (0.0 ± 1.5 + 1.3) × 10-16e · cm. This is a direct measurement of these τ form factors at q2 = 0. © 1998 Elsevier Science B.V. All rights reserved.